Kepatuhan Terhadap Hukum Islam dalam Berkendara: Signifikansi Penggunaan Helm bagi Pengendara Sepeda Motor - Almurtaqi, Moch Ridwan (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
This study aims to explore the significance of helmet use for motorcyclists in the perspective of Islamic law. Using a descriptive phenomenological approach, this study found that wearing a helmet for motorcyclists on the road is mandatory. This regulation is the implementation of several nashas and fiqh rules that have long been formulated and used as a consideration in determining Islamic law. As stated in Article 57 paragraph (1) jo paragraph (2) of Law No. 22 Year 2009 on Road Traffic and Transport (Law No. 22/2009), wearing a helmet is an effort to protect life and mind as intended in maqashid Sharia. In addition, wearing a helmet is also an effort to avoid doing dlarar, as the hadith of the Prophet SAW which prohibits doing dlarar. Finally, wearing a helmet is a form of obedience to government regulations, in accordance with the command to obey ulil amri as long as it does not conflict with Islamic law as regulated in the text of the Qur'an.